The DIVING3D survey – Deep Integral Field Spectrograph View of Nuclei of Galaxies – I. Definition and sample presentation. Issue 4 (8th January 2022) - Steiner, J E; Menezes, R B; Ricci, T V; da Silva, Patrícia; Cid Fernandes, R; Vale Asari, N; Carvalho, M S; May, D; Coelho, Paula R T; de Amorim, A L
ABSTRACT: We present the Deep Integral Field Spectrograph View of Nuclei of Galaxies (DIVING 3D ) survey, a seeing-limited optical 3D spectroscopy study of the central regions of all 170 galaxies in the Southern hemisphere with B < 12.0 and | b | > 15 ○ . Most of the observations were taken with the Integral Field Unit of the Gemini Multi-Object Spectrograph, at the Gemini South telescope, but some are also being taken with the Southern Astrophysical Research Telescope (SOAR) Integral Field Spectrograph. The DIVING 3D survey was designed for the study of nuclear emission-line properties, circumnuclear (within scales of hundreds of pc) emission-line properties, stellar and gas kinematics, and stellar archaeology. The data have a combination of high spatial and spectral resolution not matched by previous surveys and will result in significant contributions for studies related to, for example, the statistics of low-luminosity active galactic nuclei, the ionization mechanisms in low-ionization nuclear emission-line regions, and the nature of transition objects, among other topics.